Strategi Bisnis Dengan Menggunakan Analisis Swot Dengan Model Supply Chain Logistik Untuk Meningkatkan Penjualan Retail Pada Pt Xyz - Pradana Wibowo Santosa dan Eddy Herjanto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
In a SWOT analysis, the company must rely on their strengths to assist them with any threats or weaknesses that occur within the company. If their strengths are used to their advantage they can be implemented to help in avoiding new threats in the future and therefore the company will not be disrupted in its everyday procedures. The company which was used in this present analysis was PT . XYZ. This business identified that threats and weaknesseswere occurring and causing issues within the company. The method performed in this study was an analysis of the basic strategy of supply chain management and value chain analysis. After these two analysis had been completed they were then grouped into a SWOT analysis of IFE and EFE matrix from the company PT . XYZ. The results of the present study found the main cause of the weaknesses and threats in PT . XYZ was the substitution of products, threats, and competitors. In conclusion, it is therefore essential to take action to resolve these issues by using the SWOT analysis.